Enhanced Carbon Dioxide Oxidative Dehydrogenation of 1‐Butene by Iron‐Doped Ordered Mesoporous Alumina. Issue 24 (23rd November 2017) - Yan, Bing; Gao, Yue; Wang, Bolong; Fan, Xingting; Alam, Fakhre; Li, Jian; Jiang, Tao
Abstract: Iron‐doped ordered mesoporous alumina (meso‐FeAl) was synthesized through a "one‐pot" method and used in the synthesis of 1, 3‐butadiene (BD) through the oxidative dehydrogenation of 1‐butene by using CO2 as a soft oxidant. X‐ray diffraction, N2 adsorption, and transmission electron microscopy results confirmed the ordered mesoporous structure of the meso‐FeAl catalyst with a high specific surface area and a large pore volume. The results also revealed that iron species were highly dispersed inside the alumina matrix. Relative to the Fe2 O3 ‐impregnated meso‐Al2 O3 catalyst and the conventional Fe2 O3 /γ‐Al2 O3 catalyst, meso‐FeAl showed excellent catalytic activity, good stability, and high selectivity for the synthesis of BD. The structural properties as well as the form of the iron species existing in the meso‐FeAl matrix positively contributed to the performance of the catalyst. Abstract : In the matrix : Highly dispersed iron‐doped ordered mesoporous alumina is synthesized and used as an excellent catalyst for the oxidative dehydrogenation of 1‐butene with the use of carbon dioxide. The structural properties as well as the existing form of the iron species in the catalyst are found to play a key role in the reaction.